Conformational plasticity and evolutionary analysis of the myotilin tandem Ig domains - Vid Puž (Nature Portfolio, 2017)
Abstract Myotilin is a component of the sarcomere where it plays an important role in organisation and maintenance of Z-disk integrity. This involves direct binding to F-actin and filamin C, a function mediated by its Ig domain pair. While the structures of these two individual domains are known, information about their relative orientation and flexibility remains limited. We set on to characterise the Ig domain pair of myotilin with emphasis on its molecular structure, dynamics and phylogeny. First, sequence conservation analysis of myotilin shed light on the molecular basis of myotilinopathies and revealed several motifs in Ig domains found also in I-band proteins. In particular, a highly conserved Glu344 mapping to Ig domain linker, was identified as a critical component of the inter-domain hinge mechanism. Next, SAXS and molecular dynamics revealed that Ig domain pair exists as a multi-conformation species with dynamic exchange between extended and compact orientations. Mutation of AKE motif to AAA further confirmed its impact on inter-domain flexibility. We hypothesise that the conformational plasticity of the Ig domain pair in its unbound form is part of the binding partner recognition mechanism.